In Patients with Chronic Kidney Disease Short Term Blood Pressure Variability is Associated with the Presence and Severity of Sleep Disorders - Martino F. Pengo; Donatella Ioratti; Valeria Bisogni; Verdiana Ravarotto; Barbara Rossi; Luciana Bonfante; Francesca Simioni; Federico Nalesso; Giuseppe Maiolino; Lorenzo A. Calò (Karger Publishers, 2017)
Background/Aims: In chronic kidney disease (CKD) patients blood pressure variability (BPV) is associated with poor outcome. Sleep disturbances alter BP profiles in hypertensives but their influence on BPV in CKD patients is unknown. We screened a cohort of CKD/ESRD patients to investigate whether sleep quality impacts on BPV. Methods: Consecutive CKD patients' sleep quality was assessed using validated questionnaires (Epworth Sleepiness Scale-ESS); International Restless legs scale-IRLS; Functional Outcomes of Sleep Questionnaire-FOSQ: Insomnia Severity Index-ISI; STOP-Bang). All patients underwent ambulatory blood pressure measurement. Results: 104 out of 143 enrolled patients (78.32% stage-3 CKD; 10.49% Stage-4; 11.19% Stage-5; 6.99% ESRD-under dialysis) completed all the questionnaires. 95.8% were hypertensives, 70% were non-dippers and 27.8% had resistant hypertension. STOP-Bang>4 proved sleep disorders in 84.84% of patients. Patients with IRLS>10 had greater diastolic nocturnal standard deviation (DNSD) and a trend (p=0.05) for systolic nocturnal SD (SNSD). Patients with ISI>14 had greater SNSD and in 28.8% FOSQ showed severely impaired sleep quality. Their systolic nocturnal BPV was significantly greater. ISI was independently associated with SNSD. FOSQ and diastolic nocturnal BPV were negatively correlated at the bivariate analysis and FOSQ independently predicts systolic nocturnal BPV at multivariate regression analysis. Conclusions: In CKD patients impaired sleep quality increases BPV, might contribute to their disease progression and worsen prognosis. Searching for sleep problems in CKD patients could help planning their treatment of sleep problems contributing to CV risk reduction. Our data provide the rationale working hypothesis for the need of studies with larger number of patients aimed to demonstrate improved outcome of CKD progression and CV risk with the treatment also of sleep disorders.